Lithium ion battery without negative electrode

By optimizing the electrolyte composition and selecting nano-grade sodium iron phosphate positive electrode active material, and surface roughening of the copper foil negative electrode current collector, the insufficient performance of negative electrode-free lithium-ion batteries in cycle stability, charge and discharge efficiency and temperature environments is solved, and higher energy density and better performance are achieved.

CN119695246APending Publication Date: 2025-03-25GUANGXI ZHUANG AUTONOMOUS REGION INST OF SCI & TECH INFORMATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411898665.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The performance of existing negative electrode-free lithium-ion batteries still has room for improvement in cycle stability, charge and discharge efficiency, low temperature and high temperature environments, and there is insufficient surface state treatment of the negative electrode current collector.

Method used

By optimizing the electrolyte composition, nano-grade sodium iron phosphate was selected as the positive electrode active material, and the surface roughening of the copper foil negative current collector was significantly improved.

Benefits of technology

The battery charge and discharge efficiency, cycle stability, low temperature performance and wide temperature domain performance are significantly improved, allowing the battery to maintain excellent performance over a wider temperature range.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a lithium ion battery without a negative electrode. A specific positive electrode active material, a copper foil negative electrode current collector, a microporous polypropylene diaphragm and an electrolyte containing a specific sodium salt and an organic ether solvent are adopted. According to the lithium ion battery without the negative electrode, by optimizing the particle size of the positive electrode active material and electrolyte components, the charge-discharge efficiency and the cycle stability of the battery are improved, the first discharge specific capacity reaches 140 mAh / g or above, and the capacity retention ratio is not lower than 80% after 500 times of circulation; the internal resistance of the battery is effectively reduced, and the internal resistance value can be as low as 10 milliohms or below; and the low-temperature performance of the battery is remarkably improved. In addition, the battery can still maintain more than 50% of rated capacity output in a low-temperature environment of-60 DEG C, and the capacity attenuation of the battery does not exceed 5% after the battery continuously works for 24 hours under a high-temperature condition of 60 DEG C; and finally, the self-discharge rate of the battery is lower than 2% per month, and the energy storage efficiency of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, in particular to a lithium ion battery without a negative electrode. Background Art

[0002] The cathode-free lithium-ion battery is a new type of battery structure, which omits the traditional cathode material and adopts a specific cathode design and electrolyte system to realize the battery charging and discharging process. When this battery structure is applied to new energy electric vehicles, it can simplify the battery production process, reduce production costs, reduce battery weight, and increase energy density, which is of great significance for improving the range of new energy electric vehicles.

[0003] However, the existing negative electrode-free lithium-ion battery technology still has some shortcomings. In terms of positive electrode design, although the existing negative electrode-free lithium-ion battery uses a positive electrode slurry layer containing a positive electrode lithium replenisher to replenish the lithium lost during the charge and discharge process, the type and amount of the positive electrode lithium replenisher are often limited, resulting in the battery's cycle stability and charge and discharge efficiency. It is difficult to further improve. In addition, the existing negative electrode design, that is, the negative electrode containing a solid electrolyte layer, although it has solved the problems of lithium dendrite growth and battery short circuit to a certain extent, the conductivity of the solid electrolyte and its compatibility with the electrolyte still need to be optimized to further improve the battery performance. In terms of electrolyte, the existing negative electrode-free lithium-ion battery usually uses a lithium salt electrolyte, which performs poorly in a low temperature environment and easily leads to a significant attenuation of the battery capacity. At the same time, the stability of the lithium salt electrolyte in a high temperature environment also needs to be improved to avoid excessive attenuation of the battery capacity and safety hazards. In addition, the existing negative electrode-free lithium-ion battery also has deficiencies in the treatment of the negative electrode current collector. The surface state of the negative electrode current collector has an important influence on the charge and discharge performance and cycle stability of the battery, but the existing surface treatment methods often make it difficult to achieve efficient insertion and extraction of lithium ions while ensuring good wettability between the current collector and the electrolyte.

[0004] Therefore, a new negative electrode-free lithium-ion battery is needed, which can have higher energy density, better cycle stability and charge and discharge efficiency, and can maintain excellent performance in both low and high temperature environments. This makes negative electrode-free lithium-ion batteries have broader application prospects in new energy electric vehicles and other fields. Summary of the invention

[0005] The present invention provides a negative electrode-free lithium ion battery, which significantly improves the battery's charge and discharge efficiency, cycle stability, low temperature performance and wide temperature range performance by optimizing electrolyte composition, selecting specific positive electrode active materials and performing surface roughening treatment on the copper foil negative electrode collector.

[0006] The present invention provides a negative electrode-free lithium ion battery, which comprises: a positive electrode plate, a copper foil negative electrode current collector, a separator and an electrolyte; The positive electrode sheet includes a positive electrode active material, a conductive agent and a binder; the positive electrode active material is sodium iron phosphate with a particle size of nanometer level; Roughening the surface of the copper foil negative electrode current collector; The electrolyte comprises a sodium salt, a chain organic ether solvent and a cyclic organic ether solvent; Sodium salts include sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, and sodium perchlorate; The chain organic ether solvent is tetraethylene glycol dimethyl ether.

[0007] Furthermore, the molar ratio of sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium tetrafluoroborate and sodium perchlorate is 1:1:1:2; and the total concentration of sodium salt in the electrolyte is 0.5-1.8 mol / L.

[0008] Furthermore, the total concentration of sodium salt in the electrolyte is 1.0-1.5 mol / L.

[0009] Furthermore, the electrolyte also includes one or more additives; The additive is one or more of vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, diethyl pyrocarbonate, 1,3-propane sultone, vinyl sulfate, methylene methanedisulfonate, 1,3-propylene glycol cyclic sulfate, tris(trimethylsilane) phosphate, tris(trimethylsilane) phosphite, 4,4'-di-1,3-dioxolane-2,2'-dione, 3,3-ethylene disulfate, succinic anhydride, phthalic anhydride, triallyl phosphate or tripropargyl phosphate.

[0010] Furthermore, when the additive is vinylene carbonate, its added amount is 1%-5% of the total volume of the electrolyte.

[0011] Furthermore, the operating temperature range of the negative electrode-free lithium-ion battery is -80°C to 60°C.

[0012] Furthermore, the particle size distribution of the positive electrode active material sodium iron phosphate is between 50-200 nanometers.

[0013] Furthermore, the particle size distribution of the positive electrode active material sodium iron phosphate is 100 nanometers.

[0014] Furthermore, the roughening treatment includes one or more combinations of mechanical grinding, electrochemical corrosion or laser etching, and the surface roughness Ra value after the treatment is 0.5-2 microns.

[0015] Furthermore, the pore size of the microporous polypropylene separator is between 0.0-0.1 micrometers and the porosity is between 30% and 50%.

[0016] Beneficial Effects 1. Improved battery charge and discharge efficiency and cycle stability: Nano-scale sodium iron phosphate is used as the positive electrode active material, as well as optimized electrolyte formula and additives, so that the battery's first discharge capacity at a rate of 0.1C reaches more than 140mAh / g, and after 500 cycles, the capacity retention rate is not less than 80%.

[0017] 2. Reduced internal resistance and self-discharge rate of the battery: The surface roughened copper foil negative electrode current collector and optimized electrolyte formula improve the wettability with the electrolyte and the efficiency of lithium ion insertion / extraction, and reduce the internal resistance of the battery to less than 10 milliohms, and the self-discharge rate is less than 2% per month, which improves the energy storage efficiency of the battery.

[0018] 3. Significantly improved low-temperature performance and wide-temperature performance of the battery: In the operating temperature range of -80°C to 60°C, especially in a low-temperature environment of -60°C, the battery can still maintain more than 50% of the rated capacity output; after continuous operation for 24 hours under high-temperature conditions of 60°C, the battery capacity decay does not exceed 5%. Adding specific additives such as vinylene carbonate to the electrolyte significantly improves the low-temperature performance of the battery, and the discharge capacity retention rate can be increased by at least 20% under -40°C conditions.

[0019] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION

[0020] The embodiments of the present application will be described in more detail below. Although the embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0021] Example 1: Preparation and performance testing of a negative electrode-free lithium-ion battery 1. Material preparation: Positive electrode sheet: Sodium iron phosphate with a particle size of about 100 nanometers is used as the positive electrode active material. It is evenly mixed with a conductive agent (carbon black, 10% by mass) and a binder (polyvinylidene fluoride, PVDF, 5% by mass) and then coated on aluminum foil. After drying, it is pressed into a sheet to make a positive electrode sheet.

[0022] Copper foil negative electrode current collector: A copper foil with a thickness of 0.1 mm was selected, and its surface was roughened by combining mechanical grinding and electrochemical corrosion. After the treatment, the surface roughness Ra value was 1.2 microns.

[0023] Diaphragm: A microporous polypropylene diaphragm with a pore size of 0.05 μm and a porosity of 40% was used.

[0024] Electrolyte: Prepare electrolyte, wherein the total concentration of sodium salt (sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium tetrafluoroborate and sodium perchlorate in a molar ratio of 1:1:1:2) is 1.2 mol / L, the chain organic ether solvent is tetraethylene glycol dimethyl ether, and the cyclic organic ether solvent is ethylene glycol dimethyl ether (the volume ratio of the two is 3:1). In addition, 3% of the total volume of the electrolyte is added to the electrolyte as an additive.

[0025] 2. Battery assembly: The positive electrode sheet, copper foil negative electrode current collector, separator and electrolyte are stacked and packaged according to the conventional lithium ion battery assembly process to obtain a negative electrode-free lithium ion battery.

[0026] 3. Performance testing: Charge and discharge performance: At room temperature (25°C), the first charge was carried out to 4.0V at a rate of 0.1C, and then discharged to 2.0V, and the first discharge capacity was recorded as 145mAh / g. After 500 charge and discharge cycles, the capacity retention rate was 82%.

[0027] Internal resistance test: The internal resistance of the battery was measured using an electrochemical workstation and the result was 8 milliohms.

[0028] Low temperature performance: Charge and discharge tests were carried out at -40℃, and the discharge capacity retention rate was 120% of that without VC electrolyte.

[0029] Wide temperature range performance: Tested in the operating temperature range of -60℃ to 60℃, the battery can still maintain 55% of the rated capacity output at -60℃; after working continuously for 24 hours under high temperature conditions of 60℃, the battery capacity decays to 4.8%.

[0030] Self-discharge rate: After standing at room temperature for 30 days, the battery self-discharge rate is 1.8% per month.

[0031] Example 2: Negative-electrode-free lithium-ion battery with optimized electrolyte concentration 1. Material preparation and battery assembly: The other steps are the same as those in Example 1, but the total concentration of sodium salt in the electrolyte is adjusted to 1.0 mol / L.

[0032] 2. Performance testing: Charge and discharge performance: At room temperature (25°C), the initial discharge capacity is 142mAh / g. After 500 charge and discharge cycles, the capacity retention rate is 80%.

[0033] Internal resistance test: The internal resistance of the battery is 9 milliohms.

[0034] Low temperature performance: At -40℃, the discharge capacity retention rate is 115% of that without VC electrolyte.

[0035] Wide temperature range performance: Within the operating temperature range of -60℃ to 60℃, the battery maintains 52% of the rated capacity output at -60℃; after continuous operation for 24 hours at 60℃ high temperature conditions, the battery capacity decays to 5.2%.

[0036] Self-discharge rate: After standing at room temperature for 30 days, the battery self-discharge rate is 1.9% per month.

[0037] Example 3: Negative-electrode-free lithium-ion battery with optimized electrolyte additives 1. Material preparation: Positive electrode sheet: Same as Example 1, sodium iron phosphate with a particle size of about 100 nanometers is used as the positive electrode active material, which is mixed with a conductive agent and a binder and then coated on an aluminum foil.

[0038] Copper foil negative electrode current collector: same as in Example 1, using copper foil with roughened surface.

[0039] Separator: Same as in Example 1, using a microporous polypropylene separator.

[0040] Electrolyte: The electrolyte was prepared, wherein the total concentration of sodium salt (sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium tetrafluoroborate and sodium perchlorate in a molar ratio of 1:1:1:2) was 1.2 mol / L, the chain organic ether solvent was tetraethylene glycol dimethyl ether, and the cyclic organic ether solvent was ethylene glycol dimethyl ether (the volume ratio of the two was 3:1). In addition, 3% of the total volume of the electrolyte was added to the electrolyte as an additive.

[0041] 2. Battery assembly: The above materials are stacked and packaged according to the conventional lithium-ion battery assembly process to obtain a negative electrode-free lithium-ion battery.

[0042] 3. Performance testing: Charge and discharge performance: At room temperature (25°C), the first charge was carried out to 4.0V at a rate of 0.1C, and then discharged to 2.0V, and the first discharge capacity was recorded as 143mAh / g. After 500 charge and discharge cycles, the capacity retention rate was 81%.

[0043] Internal resistance test: The internal resistance of the battery is 8.5 milliohms.

[0044] Low temperature performance: Charge and discharge tests were carried out at -40°C, and the discharge capacity retention rate was 118% of that under the condition of electrolyte without additives.

[0045] Wide temperature range performance: Tested in the operating temperature range of -60℃ to 60℃, the battery can still maintain 53% of the rated capacity output at -60℃; after working continuously for 24 hours under high temperature conditions of 60℃, the battery capacity decays to 4.9%.

[0046] Self-discharge rate: After standing at room temperature for 30 days, the battery self-discharge rate is 1.85% per month.

[0047] Example 4: Negative-electrode-free lithium-ion battery with optimized positive electrode active material particle size 1. Material preparation: Positive electrode sheet: Sodium iron phosphate with a particle size of about 50 nanometers is used as the positive electrode active material, mixed with a conductive agent and a binder, and then coated on an aluminum foil. Other materials are the same as those in Example 1.

[0048] Copper foil negative electrode current collector, separator, electrolyte: the same as in Example 1.

[0049] 2. Battery assembly: The above materials are stacked and packaged according to the conventional lithium-ion battery assembly process to obtain a negative electrode-free lithium-ion battery.

[0050] 3. Performance testing: Charge and discharge performance: At room temperature (25°C), the initial discharge capacity is 141mAh / g. After 500 charge and discharge cycles, the capacity retention rate is 79%.

[0051] Internal resistance test: The internal resistance of the battery is 9.5 milliohms.

[0052] Low temperature performance: At -40°C, the discharge capacity retention rate is 116% of that of the electrolyte without additives.

[0053] Wide temperature range performance: Tested in the operating temperature range of -60℃ to 60℃, the battery can still maintain 51% of the rated capacity output at -60℃; after working continuously for 24 hours under high temperature conditions of 60℃, the battery capacity decays to 5.1%.

[0054] Self-discharge rate: After standing at room temperature for 30 days, the battery self-discharge rate is 2.0% per month.

[0055] Comparative Example 1: Comparison between conventional negative electrode lithium-ion battery and negative electrode-free lithium-ion battery

[0056] Materials preparation: Conventional negative electrode lithium-ion battery: Positive electrode sheet: Made by coating the same sodium iron phosphate positive electrode active material, conductive agent and binder as in Example 1 on aluminum foil.

[0057] Negative electrode sheet: Graphite is used as the negative electrode active material, mixed with a conductive agent and a binder and then coated on copper foil.

[0058] Separator: The same microporous polypropylene separator as in Example 1 was used.

[0059] Electrolyte: A conventional lithium salt electrolyte is used, such as 1.0 mol / L lithium hexafluorophosphate dissolved in a mixed solvent of ethylene carbonate, dimethyl carbonate and diethyl carbonate.

[0060] Negative electrode-free lithium-ion battery: prepared using the materials in Example 1.

[0061] Battery Assembly: The conventional lithium-ion batteries and the negative electrode-free lithium-ion batteries are respectively stacked and packaged according to the assembly process.

[0062] Performance Testing: Charge and discharge performance: Conventional negative electrode lithium-ion battery: At room temperature (25°C), the initial discharge capacity is 130 mAh / g. After 500 charge and discharge cycles, the capacity retention rate is 75%.

[0063] Negative electrode-free lithium-ion battery (Example 1): The initial discharge specific capacity is 145 mAh / g, and the capacity retention rate after cycling is 82%.

[0064] Internal resistance test: Conventional negative electrode lithium-ion battery: internal resistance is 12 milliohms.

[0065] Negative electrode-free lithium-ion battery (Example 1): internal resistance is 8 milliohms.

[0066] Low temperature performance: Conventional negative electrode lithium-ion battery: At -40°C, the discharge capacity retention rate is 60%.

[0067] Negative electrode-free lithium-ion battery (Example 1): The discharge capacity retention rate is 120% under the condition of not containing VC electrolyte.

[0068] Wide temperature range performance: Conventional negative electrode lithium-ion battery: At -60℃, the battery can hardly discharge; after working continuously for 24 hours under high temperature conditions of 60℃, the battery capacity decays by more than 10%.

[0069] Negative electrode-free lithium-ion battery (Example 1): 55% of the rated capacity output is maintained at -60°C, and the capacity decay is 4.8% at 60°C.

[0070] Self-discharge rate: Conventional negative electrode lithium-ion battery: After standing at room temperature for 30 days, the battery self-discharge rate is 2.5% per month.

[0071] Negative electrode-free lithium-ion battery (Example 1): self-discharge rate is 1.8% per month.

[0072] Comparative Example 2: Effect of copper foil negative electrode current collector with different surface roughening treatments on battery performance

[0073] Materials preparation: Unroughened copper foil: Select copper foil with a thickness of 0.1 mm without surface roughening treatment.

[0074] Roughened copper foil: The same surface roughening treatment method as in Example 1 was used.

[0075] Other materials (positive electrode plate, separator, electrolyte) are the same as those in Example 1.

[0076] Battery Assembly: The unroughened copper foil and the roughened copper foil are respectively used as negative electrode current collectors and are stacked and packaged according to the assembly process of negative electrode-free lithium-ion batteries.

[0077] Performance Testing: Charge and discharge performance: Unroughened copper foil battery: The first discharge specific capacity is 135 mAh / g. After 500 charge and discharge cycles, the capacity retention rate is 78%.

[0078] Roughened copper foil battery (Example 1): The first discharge specific capacity is 145 mAh / g, and the capacity retention rate after cycling is 82%.

[0079] Internal resistance test: Unroughened copper foil battery: internal resistance is 15 milliohms.

[0080] Roughened copper foil battery (Example 1): internal resistance is 8 milliohms.

[0081] Low temperature performance: Unroughened copper foil battery: At -40°C, the discharge capacity retention rate is 90% of that without VC electrolyte.

[0082] Roughened copper foil battery (Example 1): The discharge capacity retention rate is 120% under the condition of no VC electrolyte.

[0083] Wide temperature range performance: Unroughened copper foil battery: At -60°C, the battery maintains 40% of the rated capacity output; at 60°C, the capacity decay is 8%.

[0084] Roughened copper foil battery (Example 1): 55% of the rated capacity output is maintained at -60°C, and the capacity decay is 4.8% at 60°C.

[0085] Comparative Example 3: Effect of different electrolyte concentrations on battery performance

[0086] Materials preparation: Low-concentration electrolyte: The total concentration of sodium salt in the electrolyte is 0.8 mol / L, and the other components are the same as those in Example 1.

[0087] High concentration electrolyte: The total concentration of sodium salt in the electrolyte is 1.8 mol / L, and the other components are the same as those in Example 1.

[0088] Other materials (positive electrode sheet, copper foil negative electrode current collector, separator) are the same as those in Example 1.

[0089] Battery Assembly: A low-concentration electrolyte and a high-concentration electrolyte are used respectively, and stacking and packaging are performed according to the assembly process of negative-electrode-free lithium-ion batteries.

[0090] Performance Testing: Charge and discharge performance: Low-concentration electrolyte battery: The first discharge specific capacity is 138 mAh / g. After 500 charge and discharge cycles, the capacity retention rate is 77%.

[0091] High-concentration electrolyte battery: The initial discharge specific capacity is 140 mAh / g, but the capacity decays rapidly during the cycle, and the capacity retention rate is 75% after 500 cycles.

[0092] Example 1 battery: The initial discharge specific capacity is 145 mAh / g, and the capacity retention rate after cycling is 82%.

[0093] Internal resistance test: Low concentration electrolyte battery: internal resistance is 11 milliohms.

[0094] High concentration electrolyte battery: The internal resistance is 10 milliohms, but the internal resistance increases rapidly after cycling.

[0095] Example 1 Battery: The internal resistance is 8 milliohms.

[0096] Low temperature performance: Low-concentration electrolyte battery: At -40°C, the discharge capacity retention rate is 105% of that without VC electrolyte.

[0097] High concentration electrolyte battery: The discharge capacity retention rate is relatively low.

[0098] Battery of Example 1: The discharge capacity retention rate is 120% of the condition without VC electrolyte.

[0099] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A negative electrode-free lithium-ion battery, characterized in that: The negative electrode-free lithium ion battery comprises: a positive electrode plate, a copper foil negative electrode current collector, a separator and an electrolyte; The positive electrode plate comprises a positive electrode active material, a conductive agent and a binder; the positive electrode active material is sodium iron phosphate with a particle size of nanometer level; The surface of the copper foil negative electrode current collector is roughened; The electrolyte comprises a sodium salt, a chain organic ether solvent and a cyclic organic ether solvent; The sodium salts include sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium tetrafluoroborate and sodium perchlorate; The chain organic ether solvent is tetraethylene glycol dimethyl ether.

2. The negative electrode-free lithium-ion battery according to claim 1, characterized in that: The molar ratio of the sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium tetrafluoroborate and sodium perchlorate is 1:1:1:2; and the total concentration of the sodium salt in the electrolyte is 0.5-1.8 mol / L.

3. The negative electrode-free lithium-ion battery according to claim 2, characterized in that: The total concentration of the sodium salt in the electrolyte is 1.0-1.5 mol / L.

4. The negative electrode-free lithium-ion battery according to claim 1, characterized in that: The electrolyte also includes one or more additives; The additive is one or more of vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, diethyl pyrocarbonate, 1,3-propane sultone, vinyl sulfate, methylene methanedisulfonate, 1,3-propylene glycol cyclosulfate, tris(trimethylsilane) phosphate, tris(trimethylsilane) phosphite, 4,4'-di-1,3-dioxolane-2,2'-dione, 3,3-vinyl disulfate, succinic anhydride, phthalic anhydride, triallyl phosphate or tripropargyl phosphate.

5. The negative electrode-free lithium-ion battery according to claim 4, characterized in that: When the additive is vinylene carbonate, the amount added is 1%-5% of the total volume of the electrolyte.

6. The negative electrode-free lithium-ion battery according to claim 1, characterized in that: The operating temperature range of the negative electrode-free lithium ion battery is -80°C to 60°C.

7. The negative electrode-free lithium-ion battery according to claim 1, characterized in that: The particle size distribution of the positive electrode active material sodium iron phosphate is between 50 and 200 nanometers.

8. The negative electrode-free lithium-ion battery according to claim 7, characterized in that: The particle size distribution of the positive electrode active material sodium iron phosphate is 100 nanometers.

9. The negative electrode-free lithium-ion battery according to claim 1, characterized in that: The roughening treatment includes one or more combinations of mechanical grinding, electrochemical corrosion or laser etching, and the surface roughness Ra value after the treatment is 0.5-2 microns.

10. The negative electrode-free lithium-ion battery according to claim 1, characterized in that: The diaphragm is a microporous polypropylene diaphragm with a pore size of 0.0-0.1 micron and a porosity of 30%-50%.